2017
DOI: 10.1038/s41598-017-00426-y
|View full text |Cite
|
Sign up to set email alerts
|

PET Radiomics in NSCLC: state of the art and a proposal for harmonization of methodology

Abstract: Imaging with positron emission tomography (PET)/computed tomography (CT) is crucial in the management of cancer because of its value in tumor staging, response assessment, restaging, prognosis and treatment responsiveness prediction. In the last years, interest has grown in texture analysis which provides an “in-vivo” lesion characterization, and predictive information in several malignances including NSCLC; however several drawbacks and limitations affect these studies, especially because of lack of standardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(104 citation statements)
references
References 82 publications
(137 reference statements)
5
99
0
Order By: Relevance
“…First, our purpose was not to use specific anatomic-driven image acquisition protocols, but rather to test a wide enough range of acquisition parameter variations to be the most comprehensive and generalizable. Second, the number of RFs could be expanded with wavelet or Laplacian of Gaussian transformations, among others (32), but a recent study demonstrated higher concordance correlation coefficient values for unfiltered CT images than did the wavelet-filtered ones (33). A multitude of RFs have been proposed and evaluated (32), ranging from 15 RFs (10) to more than 1000 RFs (33), with Breast Imaging Reporting and Data System, Prostate Imaging Reporting and Data System, or Visually Accessible Rembrandt Images being semantic RFs.…”
Section: Discussionmentioning
confidence: 99%
“…First, our purpose was not to use specific anatomic-driven image acquisition protocols, but rather to test a wide enough range of acquisition parameter variations to be the most comprehensive and generalizable. Second, the number of RFs could be expanded with wavelet or Laplacian of Gaussian transformations, among others (32), but a recent study demonstrated higher concordance correlation coefficient values for unfiltered CT images than did the wavelet-filtered ones (33). A multitude of RFs have been proposed and evaluated (32), ranging from 15 RFs (10) to more than 1000 RFs (33), with Breast Imaging Reporting and Data System, Prostate Imaging Reporting and Data System, or Visually Accessible Rembrandt Images being semantic RFs.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of the radiomics workflow increases the need to standardize computation methods (16)(17)(18)(19). Since September 2016, about 55 researchers from 19 institutions in 8 countries have participated in the Image Biomarker Standardization Initiative (IBSI), which aims at standardizing both the computation of features and the image-processing steps required before feature extraction (e.g., image interpolation and discretization).…”
Section: Guidelines For Improving Quality Of Radiomics Analysesmentioning
confidence: 99%
“…Consequently, shape-and volume-related features may constitute confounding factors. Additionally, the rationale for volume-related criteria was related to the fact that in HL typically small and large lesions co-exist, and that size affects lesion's heterogeneity (larger lesions have been reported to be more heterogeneous than the smaller ones [14][15][16]). Therefore, the rationale for volume-related criteria was aimed at identifying all potentially relevant information and discard collinear variables, without ignoring volume component that may be relevant to predict disease aggressiveness.…”
Section: Feature Selectionmentioning
confidence: 99%